HUBUNGAN PENDIDIKAN DENGAN UPAYA PENCEGAHAN COVID-19 DI DESA LAKSAMANA KECAMATAN SABAK AUH KABUPATEN SIAK - Putri Wulandini; Sukarni Sukarni (STIKes Al-Insyirah Pekanbaru, 2021)
Corona virus or better known as Covid-19 has a new variant. Where at the beginning of the emergence there was an increase in the death rate, but now it has decreased. But there are new variants that are delta, and omicron. So that efforts to prevent the spread must still be carried out properly without being ignored. The purpose of this study was to determine the relationship between education and efforts to prevent Covid-19 in Laksamana Village, Sabak Auh District, Siak Regency in 2021. The design of this study was quantitative correlation. The population is the entire community of Laksamana Village. by using purposive sampling technique, a sample of 134 people. Questionnaire instrument. The results showed that there was a significant relationship between education and prevention efforts (p=0.000). Education is expected to increase public awareness and a better understanding of Covid-19 prevention.